1980
DOI: 10.1113/jphysiol.1980.sp013496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the perception of inspiratory resistive loads during partial curarization.

Abstract: SUMMARY1. The ability of normal subjects to estimate the magnitude of resistive loads and to detect resistive loads was determined using standard psychophysical techniques. The experiments were repeated during maintained partial neuromuscular blockade with D-tubocurarine.2. During curarization the ability to detect the presence of a small inspiratory resistive load was not significantly impaired. This finding is consistent with the view that changes in the usual breath-by-breath relation between pressure and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 18 publications
(20 reference statements)
1
37
0
1
Order By: Relevance
“…Inspiratory strength training does not alter load detection but reduces the perceived magnitude of both resistive and elastic loads [4]. Conversely, globally weakening inspiratory muscle exacerbates the sense of inspiratory efforts [5,6]. This is similar to that occurring in upper limb muscles where the development of fatigue increases the perceived heaviness of a lifted object [7], and illustrates the role of respiratory muscle afferents in the genesis of respiratory sensations.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Inspiratory strength training does not alter load detection but reduces the perceived magnitude of both resistive and elastic loads [4]. Conversely, globally weakening inspiratory muscle exacerbates the sense of inspiratory efforts [5,6]. This is similar to that occurring in upper limb muscles where the development of fatigue increases the perceived heaviness of a lifted object [7], and illustrates the role of respiratory muscle afferents in the genesis of respiratory sensations.…”
mentioning
confidence: 53%
“…This result is in line with various types of data relating respiratory muscle function and respiratory sensations. Indeed, global inspiratory muscle dysfunction or fatigue, as induced by partial curarisation [6] and exhaustion following repeated maximal static inspiratory efforts [5] lead to the overestimation of inspiratory loads. Conversely, respiratory sensations seem preserved in situations where inspiratory muscle groups are altered separately.…”
mentioning
confidence: 99%
“…In subsequent experiments, these and other workers showed that breathing frequency and inspiratory duration [20], the presence or absence of respiratory muscle weakness [21] or fatigue [22] ventilatory drive [23] and length tension relationships [24] were also variables which affect respiratory sensation. The findings of these experiments are significant because they indicate that respiratory sensation and thus by extrapolation breathlessness is determined by many factors associated with the act of breathing.…”
Section: Assessment Of Magnitude Of Respiratory Loadingmentioning
confidence: 97%
“…With weakened respiratory muscles, the requirement for motor command is increased, and the perception of inspiratory force, effort, and work can be substantially magnified (54,60,61,63), even in the absence of an increase in ventilation. It is likely that simultaneous information from muscle afferents focuses and calibrates sensation from corollary discharge (42,64).…”
Section: Qualities Of Dyspneamentioning
confidence: 99%
“…Perception of breathing effort or work can be produced in the laboratory by external resistive or elastic loads (e.g., 37, 54-57), by volitional hyperpnea (e.g., 54, 58, 59), or by weakening the respiratory muscles via changes in operating length, fatigue, or partial neuromuscular blockade (60)(61)(62). With weakened respiratory muscles, the requirement for motor command is increased, and the perception of inspiratory force, effort, and work can be substantially magnified (54,60,61,63), even in the absence of an increase in ventilation.…”
Section: Qualities Of Dyspneamentioning
confidence: 99%